Phase diagram of a model for topological superconducting wires - Perez Daroca, Diego Raul; Aligia, Armando Angel (American Physical Society, 2021)
Fil: Perez Daroca, Diego Raul. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica; Argentina